Nonlinear optical studies on bioperine crystals grown by vertical Bridgman technique for photonic applications. (May 2022) - Muthuraja, A.; Bharath, D.; Murugesan, G.; Anbuselvi, D.; Kalainathan, S.
Graphical abstract: Highlights: BPN single crystal was grown by the vertical Bridgman technique. BPN belongs to the monoclinic system and having the Centro symmetric space group P 21 / n . BPN crystal is thermallystable up to 254 °C. The optical band gap energy of BPN crystal is 2.2 eV. The non-linear absorption and refraction is attributed to a multi-photon absorption and to the self-defocusing nature of the BPN crystal. The PPN sample is excited at the wavelength of 387 nm. A high intensity sharp emission peak is observed at the wavelength of 529 nm. It is observed that the BPN crystals exhibit green emission. PL study. BPN crystal shows low dielectric constant and loss and it is suitable to fabricate the photonic devices. The dislocation density of BPN crystal was grown in Bridgeman controlled system comparatively less. Z-scan experiment explores the intrinsic optical property which behaves nonlinearly such as nonlinear refractive index ( n 2  = 1.43 × 10 −11  m 2 /W) Nonlinear absorption coefficient ( β  = 8.11 × 10 −5  m/W), third order nonlinear susceptibility ( χ 3   =  1.00678 × 10 −5  esu). Abstract: Organic single crystal Bioperine (BPN) has been grown by using vertical Bridgman technique for photonic applications. The crystal structure of BPN was studied using X-ray diffraction method. Ultra violet spectroscopy shows 69% of transparency ranges from 387 nm to 1100 nm. Melting point, decomposition temperature and thermal characteristics of BPN powdered sample was analysed by TG and DT analysis. The growth pattern and etch pit density was analysed using various chemical etchants. The electron excitation of BPN was observed at the green region of 529 nm by photoluminescence studies. By adopting Z-scan method, the values of third order nonlinear susceptibility ( χ 3 ), nonlinear refractive index ( n 2 ), nonlinear absorption ( β ) were measured. The experimental calculated values are in the range of 1.006 × 10 −5  esu, 1.43 × 10 −11  m 2 /W and 8.11 × 10 −5  m/W respectively. Two figures of merit of BPN crystal W and T, have been calculated to be W = 15 > 1 and T = 1.2 < 1, respectively. The response time of BPN crystal is in milliseconds for optical switching application at lower intensity.